Clinical Approach Strategy in Managing Complex Biliary Cases: Lesson Learnt from a Tertiary Referral Private Hospital - Cosmas Rinaldi Adithya Lesmana; Maria Satya Paramitha; Yulia Estu Pratiwi; Laurentius Adrianto Lesmana (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Introduction: In the era of laparoscopic procedure, there are innovations on non-surgical management approaches for managing biliary tract disorders, such as therapeutic endoscopic retrograde cholangiopancreatography (ERCP) and interventional endoscopic ultrasound (EUS). There is still no clear consensus yet in step-approach for managing difficult  biliary disorders. Method: A retrospective endoscopy database study was conducted. Complex biliary cases which included in this study, where multi-management approach is needed, biliary obstruction accompanied with cholangitis or biliary sepsis, difficult CBD stone, recurrent CBD stone, or advanced progressive malignant biliary obstruction. Results: Sixty-one subjects in this retrospective database study were considered as complex biliary cases. In this study, 16.4% of the subjects underwent combination of therapeutic ERCP and EUS in one session based on the complexity of the case; and 8.2% of the subjects underwent therapeutic ERCP with additional single operator cholangioscopy procedure. One subject underwent rendezvous ERCP procedure through percutaneous approach. Around 4.9% of the subjects underwent EUS-guided biliary drainage procedure. Conclusion: Complex biliary cases require a good clinical approach algorithm to decide which procedure comes first based on comprehensive evaluation consists of patient’s factor, expertise, cost, and the risk of complications.